Implementasi Penambahan Nama Seseorang Pada Dokumen Kependudukan Melalui Proses Permohonan di Pengadilan Negeri (Studi Penetapan Nomor 58/PDT.P/2022/PN.TJK) - Lukmanul Hakim; Angga Alfiyan; Ilham Jodi Renovsi (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
Many requests from the community are related to the wish to add or correct names. Related to the absence of a list, lost, falsified, altered, torn, destroyed, embezzled or disabled and so on as stated in Article 13 of the Civil Code. The purpose of this study was to find out, understand, and analyze the judge's considerations in making an application for adding a name to a birth certificate at the Tanjungkarang District Court (Study of Decision No. 58/Pdt.P/2022/PN.Tjk) and to analyze the legal consequences of adding a name to a document birth certificate. The purpose of this research is to analyze the request for a change of name in a document based on a court decision. The research method uses a normative juridical approach. A valid child's birth certificate must be an authentic deed, because an authentic deed is a deed drawn up by or before a public official authorized to make the letter, with the intention of making the letter as evidence. Birth certificates are not only based on considerations of citizenship status, written evidence is needed to obtain legal certainty, to prove that a population event has indeed occurred. To have proof of registering in the status of the incident above, a person must have that event or incident at a civil registry institution, thus that person will obtain written evidence issued by the relevant agency. In this case, the Department of Population and Civil Registration can issue it.